Homotypic targeting upconversion nano-reactor for cascade cancer starvation and deep-tissue phototherapy. (March 2020) - Wang, Han; Wang, Zhaohui; Tu, Yuanbiao; Li, Yongkuan; Xu, Tian; Yang, Man; Wang, Peng; Gu, Yueqing
Abstract: Cancer starvation therapy based on catalytic chemistry of glucose oxidase (GOx) offers great potential for multimodal treatment, benefiting from both nutrition shutting-off and the oxidization product hydrogen peroxide (H2 O2 ). Herein, further optimization of such combined therapy was achieved by a cascade Nano-reactor, which was constructed by incorporating GOx into a bio-mimic upconversion nanosystem. The cascade began when GOx was delivered into tumor sites through homotypic targeting, facilitating selective starving of cancer cells and H2 O2 generation. Then, upon 980 nm laser excitation, the 470 nm light emitted by upconversion nanoparticles (NaYF4 : Yb, Tm) photolyzed H2 O2 into hydroxyl radical for phototherapy, superior to direct photolysis by blue light with limited tissue penetration depth. Meanwhile, the 800 nm emission of UCNPs was used to track the in vivo fate and tumor targeting ability of the Nano-reactor. Radionuclide imaging further confirmed the targeting of the Nano-reactor to subcutaneous 4T1 tumor and lung metastasis. Significantly enhanced therapeutic efficacy of this cascade starvation-phototherapy was validated in vitro and in vivo, suggesting the Nano-reactor as a smart, simple and strong system for cancer multimodal therapy.